The sound of a million dreams [compact disc] - Nail, David (MCA Nashville, 2011)
Among the album's twelve tracks is the single Let It Rain as well as songwriting collaborations with Keith Urban and Lady Antebellum's Charles Kelley and Dave Heywood.